Embodied Relational Process in P. Megan Andrews’ the disorientation project - Joosse, Angela (Imaginations)

(untitled) (York University, 2023)
This article offers embodied, phenomenological descriptions of the disorientation project, a solo work by dance artist P. Megan Andrews. From the position of an ongoing witness of Megan’s practice, the author reflects on how experiences of perceptual disorientation can be potent and productive, opening space for relations of care.